Heterologous Production of Human Papillomavirus L1 Capsid Protein: Systematic Review and Meta-analysis - Andre Hendrawan; Azzania Fibriani (3BIO: Journal of Biological Science, Technology and Management, 2022)
The coverage of HPV vaccination in Indonesia remains low due to the high-cost vaccination. The vaccine prices were affected by the production rate of L1, the active substance of HPV vaccines. L1 has been produced using various organisms with varying L1 production rates and immunogenicity. A systematic review and meta-analysis were conducted to determine the organism producing L1 with the highest production, treatments affecting the L1 expression rate, and immunogenicity (represented by anti-L1 IgG titer in mice). The data of L1 titer, induction period, and IgG titer were extracted from 19 articles that have passed the articles screening. The L1 titer and induction period data were used to calculate the L1 production rate, while the IgG titer was used in the immunogenicity analysis. On a 95% confidence level, the meta-analysis revealed weak evidence that E. coli produced L1 at the highest rate. The highest IgG titer was induced using L1 expressed in Saccharomyces cerevisiae, albeit insufficient evidence on 95% confidence level. Pearson’s correlation analysis showed that the concentration of glucose, IPTG, NH4+, K+, Ca2+, Mn2+, Fe2+, Zn2+, B4O72−, H2PO4−, HPO42−, Mo7O246−, and citric acid had a positive correlation with L1 production rate in E. coli. The treatment injection doses positively correlated with IgG titer in S. cerevisiae. This study reveals the mineral salts as the potential treatments to increase L1 production rates.